Mass Hysteria, Manufacturing Crisis and the Legal Reconstruction of Acceptable Exercise during a Pandemic. (3rd March 2021) - Simpson, Brian
Abstract: There is a saying in that every crisis is an opportunity. Unfortunately, this seems to be applied more to politicians seeking to extend their powers over citizens, and less to citizens attempting to imagine new forms of accountable government. The Covid-19 pandemic has created an extraordinary shift in people's freedoms in a short space of time, with little interrogation or apparent concern with the legal basis of this shift. Exercise has been one area where citizens otherwise required to stay at home can perform some freedom. Yet many of the directives are confused and contradictory in explaining what exercise is permitted. Australian examples are used to illustrate these points and question whether the law is redefining exercise in ways that are arbitrary and discriminatory for a crisis now that may impact on the future practice of exercise. Is this legal control of exercise the harbinger of new forms of social control?